On Hesperian Depression: Eugene Nielen Marais and the history of a poetical state of the soul - van Luijk, Ruben (Werkwinkel, 2014)
The article gives a brief ‘idea history’ of Hesperian melancholy a.k.a. Hesperian depression, the fleeting state of dejection that some humans and animals experience at dusk. The term was apparently coined by the South African poet and naturalist Eugene Marais (1871-1936), who noticed the phenomenon during his field observations of baboons. Marais' observations of primates were in the first place an attempt to shed more light on the evolutionary roots of the human psyche and its afflictions - not in the least his own. A personal focus seems probable in his notes on the use of euphoria-inducing substances among animals and humans, which are an evident reflection of his own morphine addiction; but also in his writings about Hesperian depression. During his lifetime, Marais only published about Hesperian depression twice, once in a very concise article in English, and once in more elaborate form in Afrikaans. The term ‘Hesperian depression’ only became more current when his manuscript on primate behaviour, The Soul of the Ape, was posthumously published in 1963. Since then, the term and its description sometimes appear in (popular) publications of paleobiologists and scholars of the evolution of human behaviour. In psychology and psychiatry, the term was introduced by the eminent American psychoanalyst William G. Niederlander, who presented it in a 1971 article in Journal of the American Psychoanalytic Association as an idea of his own. It is evident, however, that he took his cue from Marais, who thus was posthumously plagiarized.